Knowledge of prevention of lower limb atherosclerosis among patients aged 45-65 in general and vascular surgery wards - Michalik, Anna; Pająk, Celina; Hryć, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction: The occurrence of atherosclerosis in the lower limbs increases the risk of arterial disease in other vascular areas. This indicates the importance of the implementation of educational programmes for all, not only for those diagnosed with the condition. Awareness of the disease and its prevention among young and middle-aged people increases the likelihood of their being able to lead a healthy lifestyle, which in turn reduces the risk of atherosclerotic changes. Aim of the study: The main aim of the study was to conduct research among patients aged 45-65, hospitalised in general and vascular surgery wards, in order to verify their knowledge of the prevention of lower limb atherosclerosis. Materials and methods: The study was conducted between August and December 2023 among 107 patients aged 45-65 with atherosclerotic diseases who were hospitalised in the general and vascular surgery ward of the one of regional hospital in Podbeskidzie Region. The study was conducted as a survey, using a questionnaire designed by the authors. Results: Less than half of the respondents (49.5%) required hospitalisation within a year of being diagnosed with Lower Extremity Arterial Disease (LEAD). Most respondents had average knowledge of atherosclerosis (67.3%), while as many as 78.0% of respondents had good or very good knowledge of lower limb atherosclerosis prevention. The main source of knowledge about the disease was specialist doctors (67.3%). As many as 86.0% of respondents stated that their quality of life had deteriorated after developing atherosclerosis. The most common risk factors in patients were being overweight (77.6%) and obesity (49.5%). Conclusions: Patients' knowledge about the disease and its prevention is average. Patient education on prevention, especially on proper nutrition, is recommended to reduce the risk of developing atherosclerosis.